Implementasi Media Pembelajaran Audio Visual terhadap Pemahaman Siswa Kelas VII C pada Materi Wudhu di SMP Negeri 2 Kabuh - Setyowati, Siti Sundari; Nisa’, Khoirun (YASIN, 2025)
The appropriate use of learning media plays an important role in improving students’ understanding, particularly in Islamic Religious Education. This study is motivated by the low understanding of Grade VII C students at SMP Negeri 2 Kabuh regarding the topic of wudhu, which has so far been delivered mainly through lectures, despite the school having audio-visual facilities that have not been optimally utilized. The research aims to describe the implementation of audio-visual media in teaching wudhu, determine the improvement in students’ understanding after its use, and identify the supporting and inhibiting factors in its application. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The findings show that the use of audio-visual media, such as instructional videos, can improve students’ understanding, as reflected in their active participation in learning activities and better evaluation results. Supporting factors include the availability of supporting facilities and students’ enthusiasm, while inhibiting factors include limited instructional time and technical constraints. The study concludes that audio-visual media are effective in enhancing the quality of wudhu instruction at SMP Negeri 2 Kabuh.